2022
DOI: 10.1186/s12909-022-03898-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of an artificial intelligence chatbot educational program on non-face-to-face classes: a quasi-experimental study

Abstract: Background Education and training are needed for nursing students using artificial intelligence-based educational programs. However, few studies have assessed the effect of using chatbots in nursing education. Objectives This study aimed to develop and examine the effect of an artificial intelligence chatbot educational program for promoting nursing skills related to electronic fetal monitoring in nursing college students during non-face-to-face cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Ultimately, using chatbots can result in improved student outcomes and increased satisfaction. The theoretical framework of this study also suggests that chatbots can support self-directed learning (Han et al, 2022;Sharma et al, 2022). Chatbots can be programmed to provide students with resources and support for self-directed learning by recommending additional readings or providing study tips.…”
Section: Step Descriptionmentioning
confidence: 91%
“…Ultimately, using chatbots can result in improved student outcomes and increased satisfaction. The theoretical framework of this study also suggests that chatbots can support self-directed learning (Han et al, 2022;Sharma et al, 2022). Chatbots can be programmed to provide students with resources and support for self-directed learning by recommending additional readings or providing study tips.…”
Section: Step Descriptionmentioning
confidence: 91%
“…In a different perspective, it was found that there is a potential for using ChatGPT as an educational assistance tool to promote interest in education and self-directed learning, particularly in non-face-to-face situations as COVID-19 pandemic [ 13 ]. As already suggested for healthcare systems, the utilization of AI might be crucial and imperative because of its ability to enhance precision and accuracy whilst reducing the time required for various aspects of the system.…”
Section: Methodsmentioning
confidence: 99%
“…It can also be used to help medical students, doctors, nurses, and all members of the healthcare fraternity alike to know about updates and new developments in their respective fields, and can also be used as a tool of assessment to assess clinical skills (Han et al, 2022 ) thus playing a pivotal role in medical education. Chatbots like ChatGPT can be used as powerful tools to increase health literacy, especially among students and young adults (Mokmin and Ibrahim, 2021 ).…”
Section: Advantages and Applicationsmentioning
confidence: 99%